Does solo self-employment serve as a ‘stepping stone’ to employership? - Cowling, Michael Leith; Wooden, Mark (My University, 2021)
This paper examines the extent to which solo self-employment serves as a vehicle for job creation. Using panel data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, a dynamic multinomial logit model of transitions between labour market states is estimated. The empirical strategy closely follows that used in a previous study employing household data from Germany by Lechmann and Wunder (2017). Estimates of true cross-state dependence between solo self-employment and employership are obtained that are relatively small. Further, the results imply that the probability of a male worker being an employer just two years after transitioning out of solo self-employment is only about 4% (and among women, it is just 2%). The extent of both true cross- state dependence and true state dependence in employership is, however, much greater among individuals who have demonstrated a preference for self-employment in the past. This implies that pro-entrepreneurial policies that target more ‘entrepreneurial’ individuals will have more pronounced and long-term effects in stimulating job creation.
Labour Economics
Keywords: Labour market